Control systems theory and implementation - Kumarawadu, Sisil (Alpha Science International, 2010)
Control Systems: Theory and Implementation contains a comprehensive coverage of mathematical modeling of dynamical systems, analog and digital control principles, controller design and analysis, commercial microcontrollers / DSPs for control applications, and implementation of control systems using microprocessor-based systems. Theoretical contents of the book are presented as much practically oriented as possible. Most books on control systems contain extensive amount of theoretical contents but little information about the practical aspects and implementation. There are books on digital signal processing but with little emphasis on real-time control applications. Control engineering is one of the broadest sub-disciplines of Engineering that can not be covered in a single book. Too much of content in the book often makes it difficult for undergraduate students and beginners to figure out which of the contents should be the most relevant. This book starts with the basic fundamentals, modeling of dynamical systems, discusses analog and digital control theories, and practical implementation using microprocessor-based systems. The contents cover typical syllabi of a control systems undergraduate course and postgraduate level taught courses and hence in ideal text book in control systems for beginners.